Pure Experience and Nomadism in James and Deleuze - Ferro, Floriana (Scenari, 2021)
Deleuze’s attention to singularity has its roots in the Jamesian concept of the virtual, according to which pure experience is only virtually objective or subjective, but currently unqualified . It is now clear the meaning of Deleuzian “preindividual singularities” , of a difference which is preserved before individuation, representation, and conceptual generalization. As the philosopher writes in his last work, the “virtual is not something that lacks reality but something that is engaged in a process of actualization following the plane that gives it its particular reality”. This kind of virtuality coincides with nomadism, with the distribution of univocal being, free from hierarchies, capable of preserving differences through a process of repetition without a reference model.